Socio-Pedagogical Diagnostics Of The Artistic And Cultural Environment Of The Region As A Factor Of Upbringing - Necenko, Olga; Grenaderova, Larisa (Զանգակ հրատ.)
This article actualizes the problem of studying the artistic and cultural environment of the region as the factor of education, determining the means and methods of diagnosing its educational capabilities. During the research, the selection, adaptation, and development of diagnostic tools for solving the tasks were carried out. We have identified the resources of the artistic and cultural environment of the region, which are not always used to solve the problems of education. As the main resource, we see a teacher motivated for a child’s spiritual development and inclusion in the artistic and cultural environment of the region. Socio-pedagogical diagnostics of the artistic and cultural environment of the region was carried out from the standpoint of a non- physicalist approach, which involves not only a description of the components of the environment (theatrical, architectural, musical, museum and other environments), its material resources, but also monitoring of relations and values between a person and an artistic and cultural environment.
Keywords: Upbringing